COMPARISON OF CURRENT CONTROL METHODS ON CARRIER BASED VSI-PWM INVERTER DRIVES FROM LINE POWER QUALITY ASPECT - Muh. Imran Hamid; Makbul Anwari; Taufik Taufik (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2008)
This paper describes simulation result of two methods in current controlling for carrier based VSI-PWM inverter: hysteresis and ramp comparison control.  The simulation useful in selection of ASDs and generally–converter, from power quality point of view. Simulation result show that both ramp comparison and hysteresis control methods  gives difference characteristic on line voltage and line current. A ramp comparison method is better in form of lower effect on line current distortion compare with hysteresis control method. Meanwhile, for line voltage distortion, hysteresis control seen better.